Evaluation of the position of the needle tip during thoracentesis: Experimental study. Issue 28 (16th July 2021) - Shimoda, Masafumi; Morimoto, Kozo; Tanaka, Yoshiaki; Yoshimori, Kozo; Ohta, Ken
Abstract: Introduction: Thoracentesis is performed to both diagnose and/or treat pleural effusion, and several important complications of thoracentesis are occasionally observed. To assess precise thoracentesis procedures, we evaluated the position of the needle tip during thoracentesis by using a thoracentesis unit, comparing experienced and inexperienced groups. Methods: Twenty eight physicians (19 board-certified pulmonologists as an experienced group and the remaining 9 as an inexperienced group) participated at Fukujuji Hospital in January 2021. All participants performed 2 punctures with a handmade thoracentesis unit and measured the needle's angle to the midline. Results: The median distance from the needle tip to the midline when the needle was inserted 5 cm (D5) was 0.47 cm (range 0.06–1.05), and the median difference between D5 on the 1st puncture (D51st ) and D5 on the 2nd puncture (D52nd ) was 0.22 cm (range 0.00–0.69). D5 was shorter in the experienced group than in the inexperienced group (median 0.40 cm (range 0.06–0.66) vs 0.58 cm (range 0.44–1.05), P  < .001). There were no significant differences in the D51st and D52nd distances between the experienced and inexperienced groups (median 0.22 cm (range 0.00–0.40) vs 0.41 cm (range 0.04–0.69), P  = .094). When 4 areas were divided by the x-axis and y-axis, 32 punctures (55.2%) deviated to the right-upper quadrant, and 25 (86.2%) of participants made the 1st puncture and 2nd puncture in the same direction. Conclusions: All doctors should know that the needle direction might shift by approximately 1 cm, and more than half of the practitioners punctured towards the upper right.